O impacto da parceria transatlântica de comércio e investimento (TTIP) nas macrorregiões brasileiras - Silva, Mygre Lopes da (2016)
The intensification of commercial relations between the United States and the European Union started in the 1990s, in the post-Cold War period. In this context, discussions emerged regarding a Transatlantic Trade and Investment Partnership (TTIP). After the weakening of both economies, given by China's economic rise and the Subprime crisis, their relations were narrowed with the objective to form a free trade area. Thus, the aim of this study is to assess the impact of the creation of a free trade area between the United States and the European Union (EU), the TTIP, in the Brazilian economy, more specifically in the five Brazilian macro-regions. To accomplish this, the General Equilibrium model (GTAPinGAMS) was used, from the database of the General Equilibrium Analysis Project of the Brazilian Economy (PAEG). In this sense, two scenarios were estimated, being the first with the elimination of import tariffs between the EU and US, and the second with the full liberalization of trade. In the first scenario, the economic impacts in the Brazilian regions were mostly negative, affecting mainly the sectors of clothing, footwear and the textile industry. In the second scenario, the Brazilian agricultural producer and exporter sector were positively influenced. However, the clothing, footwear and the manufactured sector suffered the major efficiency losses.